THE RELATIONSHIP BETWEEN OCCUPATION, PREVENTIVE BEHAVIORS, AND ENVIRONMENTAL CONDITIONS ON THE INCIDENCE OF MALARIA IN MEKAR SARI VILLAGE - Sofiyana, Ririn Hariani; Azmi, Fahriana; Utary, Dewi; Indriyani, Ni Putu Dewi (Jurnal Biosains Pascasarjana, 2025)
Malaria is a disease that often causes health problems globally, including in Indonesia. The increasing prevalence of malaria cases can have a broad impact on the quality of life and economy and even threaten the safety of human life. This study aims to determine the relationship between occupation, preventive behavior and environmental conditions around the house to the incidence of malaria in Mekar Sari Village, West Lombok. This study used analytic observation method with cross-sectional design. The population of this study were all Mekar Sari Village residents who indicated malaria. The sampling technique used was purposive sampling using certain considerations. The data obtained were analyzed univariately and bivariately with Chi Square. The results of this study showed that most respondents had gardening jobs, a total of 26 people or (29.5%), adequate prevention behavior, a total of 39 people or 44.3%, unfavorable environmental conditions, a total of 60 people or 68.2%, and most respondents had malaria, a total of 46 people or 52.3%. There is a relationship between occupation (p-value 0.039), preventive behavior (p-value <0.001) and environmental conditions around the house on the incidence of malaria (p-value 0.019). There is a significant relationship between occupation, preventive behavior and environmental conditions on the incidence of malaria in Mekar Sari Village, West Lombok. Keywords: Occupation, Preventive Behavior, Environmental Conditions, Malaria Incidence